Needs and Trends of Rain Water Harvesting in Sri Lanka - Sayanthan, S.; Mikunthan, T.; Kannan, N.; Prabhaharan, M.; Thaneswaran, N. (International Journal of Research Studies in Agricultural Sciences (IJRSAS), 2017)
Water being one of the world’s basic resources and the most important element for lives to survive. But, because of several water related issues and population growth Sri Lanka is in a negative track in terms of water sustainability. Hence the country needs to adopt an ideal process which must leads the country towards a steady state in the case of available water. The answer should be Rain water harvesting. Even though the country has been practicing rain water harvesting for many centuries, the system was unable to satisfy the domestic needs in systemic and scientific ways until the introduction of Community Water Supply & Sanitation Project in 1996. After this initiation rain water harvesting projects were carried out by many other government and non-government organizations. Now the country has far better rain water harvesting systems. But it is essential to ensure well established rainwater harvesting systems all over the country which will make us to step in to a water rich era.
Keywords: Surface water; Ground water; Water management; Rain water harvesting; Rain water treatment; Rain water quality